IL-33/ST2 axis mediates diesel exhaust particles-induced mast cell activation - Wun-Hao Cheng; Ting-Li Zhuang; Meng-Jung Lee; Chun-Liang Chou; Bing-Chang Chen; Han-Pin Kuo; Chih-Ming Weng (Molecular Medicine)
Abstract Background Mast cells are implicated in the pathogenesis and severity of asthma in children and adults. The release of proinflammatory mediators and cytokines from activated mast cells (MC) is associated with Type 2 (T2) cell-skewed inflammation. Methods We obtained the airway tissues of Balb/c mice with or without intra-tracheal diesel exhaust particles (DEP) instillation to measure the extent of tryptase+ MCs infiltration and interleukin (IL)-33 expression. Cultured human mast cells (HMC-1) were stimulated with DEP to determine the role of aryl hydrocarbon receptor (AhR) in mediating the synthesis and release of IL-33 and type-2 cytokines. Results In the control animals, most of the MC accumulated in the submucosal vessels without expression of IL-33. Intra-tracheal DEP installation increased the number of IL-33+ MC infiltrating in the epithelial and sub-epithelial areas of mice. Human MC exposed to DEP upregulated mRNA and protein expression of IL-33. These effects were abolished by knockdown of expression of the AhR or AhR nuclear translocator (ARNT) by small interfering (si)RNA transfection. DEP also activated nuclear factor-kappa B (NF-κB) to facilitate nuclear translocation of the AhR. DEP increased MC migration and induced the synthesis and release of IL-4, IL-5, and IL-13 in MCs, and these effects were abolished by anti-ST2 antibodies. Conclusions Airborne pollutants may activate MCs to produce IL-33 via the AhR/NF-κB pathway, leading to type 2 cytokines production and enhancing MC airway epithelium-shifted migration through the autocrine or paracrine IL-33/ST2 axis.